Renal cell carcinoma with intracardiac tumor thrombus extension: Radical surgery yields 2 years of postoperative survival in a single-center study over a period of 30 years - Zacek, Pavel; Brodak, Milos; Gofus, Jan; Dominik, Jan; Moravek, Petr; Louda, Miroslav; Podhola, Miroslav; Vojacek, Jan (Frontiers in Oncology, 2023)
Background Renal cell carcinoma (RCC) with tumor thrombus extension into the right atrium (level IV) is a rare life-threatening clinical condition that can only be managed by means of a combined urological and cardiac surgical approach. The early and late outcomes of this radical treatment were analyzed in a large single-institution series over a period of 30 years. Methods In 37 patients with RCC and intracardiac tumor thrombus extension, nephrectomy was performed followed by the extraction of the intracaval and intracardiac tumor thrombus under direct visual control during deep hypothermic circulatory arrest (DHCA). Recently, in 13 patients, selective aortic arch perfusion (SAAP) was instituted during DHCA. Results In all patients, precise removal of the tumor thrombus was accomplished in a bloodless field. The mean duration of isolated DHCA was 15 ± 6 min, and 31.5 ± 10.2 min in the case of DHCA + SAAP, at a mean hypothermia of 22.7 ± 4°C. In-hospital mortality was 7.9% (3 patients). In Kaplan–Meier analysis, the estimated median survival was 26.4 months whereas the 5-year cancer-related survival rate was 51%. Conclusions Despite its complexity, this extensive procedure can be performed safely with a generally uneventful postoperative course. The use of cardiopulmonary bypass with DHCA, with the advantage of SAAP, allows for a safe, precise, and complete extirpation of intracaval and intracardiac tumor mass. Late outcomes after radical surgical treatment in patients with RCC and tumor thrombus reaching up in the right atrium in our series justify this extensive procedure.